Monitoring and Evaluation of the Use of Personal Protective Equipment (Ppe) Among Nurses in Post Pandemic Educational Hospitals - Lilis Setyowati; Marzicha Amalia Sumardiko; Erma Wahyu Mashfufa; Ollyvia Freeska Dwi Marta; Nur Aini; Sunardi (PT FORMOSA CENDEKIA GLOBAL, 2024)
Use personal protective equipment (PPE) to prevent the chain of disease transmission, especially Covid-19. This study aims to monitor and evaluate the use of PPE among nurses who work in inpatient and emergency rooms at teaching hospitals in Malang. This research uses a cross-sectional comparative analysis approach. Data were collected using hospital SOP observation sheets by the Minister of Health Regulation 27 of 2017. Using a purposive sampling technique, the sample size was 82 nurses, divided into inpatient and emergency rooms. Data analysis uses descriptive and Chi-square to analyze differences in work area use of PPE (α= 0.05). The study's results showed differences in compliance and level of risk of exposure for nurses in using PPE in emergency departments and inpatient rooms (p-value=0.009). Emergency department nurses use PPE more often according to SOP, which has a higher exposure risk than inpatient nurses.